Some time ago, I solved (just for fun) $f'(x)=\cos(f(x))$ and asked myself what the solution to the title equation $f'(x)=f(\cos(x))$ is. I see that $f$ is periodic and odd, but not how to go on after that.

(Related question: Is there a general solution for $f'(x)=f(g(x))$ with given $g$?)

  • $\begingroup$ Somehow for $x\in(0,\pi)$ I am getting the solution $f=\exp x$ which doesn't make sense. But I can't find an error... $\endgroup$ – mobiuseng Jan 28 '18 at 21:11
  • $\begingroup$ $f(x) = 0$ is a solution. $\endgroup$ – eyeballfrog Jan 28 '18 at 22:27
  • 2
    $\begingroup$ @mobiuseng You get $f = \exp x$ if you confuse $\frac{df(x)}{d\cos(x)}$ with $\frac{df(\cos(x))}{d\cos(x)}$, i.e. if you do the derivation by keeping the arguments of $f$ "hidden". $\endgroup$ – Winther Jan 28 '18 at 23:19
  • 1
    $\begingroup$ Also, $f$ does not need to be odd. Its derivative needs to be even. That means it could be an odd function plus a constant. $\endgroup$ – eyeballfrog Jan 29 '18 at 1:08

Let $x_0\in(0,\pi)$ be the solution to $x_0 = \cos(x_0)\approx 0.739$. If we let $$ f(x) = \sum_{n=0}^\infty a_n(x-x_0)^n $$ and expand the differential equation in power series, we get $$ \sum_{n=0}^\infty (n+1)a_{n+1}(x-x_0)^n = \sum_{n=0}^\infty a_n(\cos(x)-x_0)^n = \sum_{n=0}^\infty a_n(x-x_0)^n\left[\frac{\cos(x)-\cos(x_0)}{x-x_0}\right]^n. $$ Now $([\cos(x)-\cos(x_0)]/[x-x_0])^n$ can itself be written as some power series $\sum_{m=0}^\infty b_{mn}(x-x_0)^m$. So we have $$ \sum_{n=0}^\infty (n+1)a_{n+1}(x-x_0)^n =\sum_{n=0}^\infty a_n(x-x_0)^n\left[\frac{\cos(x)-\cos(x_0)}{x-x_0}\right]^n \\= \sum_{n=0}^{\infty}\sum_{m=0}^\infty a_nb_{mn}(x-x_0)^{n+m}= \sum_{k=0}^\infty \left[\sum_{n=0}^ka_nb_{(k-n)n}\right](x-x_0)^k. $$ Swapping the dummy indices $k$ and $n$ then gives a recursion relation for the coefficients: $$ a_{n+1} = \frac{1}{n+1}\sum_{k=0}^n a_kb_{(n-k)k}. $$ Unfortunately I'm not aware of a nice expression for the $b_{mn}$. Calculating the first 30 terms numerically and taking advantage of symmetry gives me this for $f(x)$


and a comparison of $f'(x)$ (blue) with $f(\cos(x))$ (yellow)

f'(x) vs f(cos(x))

The series matches up well out until about $x_0 + 1.4$, and applying the root test to the coefficients suggests it has a finite radius of convergence of about $1.8$, so I think this is getting the right solution. This is consistent with a function that has a singularity at $i\pi/2$, so it's possible there's a global solution on $\mathbb R$ that this method can't quite catch. All other solutions are constant multiples of this one (which is $f(x_0) = 1$).

EDIT: Actually, since this method does give $f(x)$ for $x\in [-1,1]$, we have $f(\cos(x))$ for all $x\in \mathbb R$. We should be able to get the function on the rest of $\mathbb R$ by just integrating $f(\cos(x))$. This gives a function of the form $f(x) = f(0) + f(0)x + g(x)$, where $g(x)$ is some oscillatory function with period $2\pi$ and average value $0$ that looks sort of like $\sin(x)$. Not sure how much better we can do analytically.

  • $\begingroup$ @YuriyS By the initial conditions, presumably. This is a differential equation, after all. $\endgroup$ – eyeballfrog Jan 29 '18 at 8:19
  • $\begingroup$ @YuriyS I chose $f(x_0) = 1$, as mentioned under the plots. $\endgroup$ – eyeballfrog Jan 29 '18 at 10:13
  • $\begingroup$ I apologise, I missed this $\endgroup$ – Yuriy S Jan 29 '18 at 10:15

I am getting an absurd answer, obviously doing something wrong, but can't see where. So, here is my (wrong) solution for the record and to find the error.

Let $x\in(0,\pi)$ and $z = \cos x$, $dz/dx = -\sin x$ and $x = \arccos z$.

$$ \frac{df}{dx} = \frac{df}{dz}\frac{dz}{dx} = -\sin x\frac{df}{dz} $$


$$ -\sin x \frac{df}{dz} = -\sin(\arccos z)\frac{df}{dz}=-\sqrt{1-z^2}\frac{df}{dz} $$

From here:

$$ \frac{df}{dz} = -\frac{1}{\sqrt{1-z^2}}f(z) $$

$$ \frac{df}{f} = -\frac{dz}{\sqrt{1-z^2}}\quad\Rightarrow\quad \ln f=\arccos z $$

$$ f = \exp\left(\arccos z\right)=\exp x $$

So, $z$ and $x$ have one-to-one correspondence for $x\in(0,\pi)$. $z^2<1$, so I've not divided by zero. $f$ can be zero --- by dividing by it I probably lost some solution, but it shouldn't have led to such absurdity...

  • 3
    $\begingroup$ The problem is that your $df/dz$ is evaluated at $\cos^{-1}(z)$, not $z$. $\endgroup$ – eyeballfrog Jan 28 '18 at 22:00
  • $\begingroup$ @eyeballfrog Ah, now I see it! Then, of course I was getting $df/dx|_{\cos x} = f(\cos x)$ and $f(x) = \exp x$ would be the right answer for this problem. Thanks! $\endgroup$ – mobiuseng Jan 29 '18 at 6:45

Too long for a comment.

Observe that $f'(x+2\pi n)=f'(x)$ for all $n\in\mathbb Z$, so $f(x+2\pi n)=f(x)+n\varepsilon$ for some constant $\varepsilon$ (which we assume nonzero). If you let $f(x)=(\varepsilon/2\pi)(1+x+g(x))$, then this implies $g(x+2\pi n)=g(x)$, i.e. $2\pi$ periodicity. If we assume that $g$ is bounded, then we obtain the result $$ f(x)\sim \varepsilon x/2\pi,\qquad |x|\to\infty, $$ provided $\varepsilon\neq 0$. Here, the lower order term $g$ solves the equation $$ g'(x)=\cos(x)+g(\cos(x)). $$ The other case $\varepsilon=0$ is the $2\pi$-periodicity of $f(x)$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.